041 Determinants of prolonged time to diagnosis in relapsing-remitting multiple sclerosis in Scotland. Issue 6 (27th May 2022) - Brown, Fraser; Kearns, Patrick; Martin, Sarah-Jane; Connick, Peter; Hunt, David; Chandran, Siddharthan
Abstract : Background: There is increasing emphasis on earlier diagnosis in patients with relapsing remitting multiple sclerosis (RRMS) as evidence is accumulating that earlier treatment reduces long-term disability accumu- lation. Much inter-individual variability in time to diagnosis remains unexplained. Objectives: To examine factors associated with longer time to diagnosis in a cohort of adult patients diagnosed with RRMS in Scotland between January 2016 and February 2019. Methods: Clinical and demographic features were collected as part of an incidence cohort study. Time to diagnosis was defined as interval between date of first symptom to date of diagnosis and considered prolonged if it was greater than the median value. Age at onset, sex, weight, smoking status, employ- ment status, socioeconomic status and onset symptom type were examined for association with time to diagnosis using logistic regression. Results: We recruited 440 patients. Median time to diagnosis was 1.75 years. Current employment (OR 2.016 [1.186–3.428] p=0.010) was associated with longer time to diagnosis. We found no association with other variables measured. Conclusions: Time to diagnosis in RRMS in Scotland is employment status-dependent. A considerable proportion of variance in time to diagnosis remains unexplained in RRMS. fraser@tonnard.co.uk